Auditoría de Gestión a la Unidad Educativa Nuestra Señora de Fátima de la ciudad de Riobamba, periodo 2022. - León Coello, Carina Lisbeth (2023)
This research was carried out with the objective of developing a Management Audit of the Educational Unit Nuestra Señora de Fátima in the city of Riobamba, period 2022. It was developed by applying the deductive and analytical method, based on a qualitative approach to description, data collection and analysis and a quantitative approach when applying management indicators to analyse the data provided. On the other hand, the audit was developed in three phases: preliminary planning aims at getting to know the Institution by applying techniques such as surveys, interviews and observation, while in the planning phase, the evaluation of internal control was developed using the Committee of Sponsoring Organizations of the Treadway (COSO) III Model; in the execution phase, the degree of compliance of the Institution's processes in the administrative area was evaluated, which allowed for the identification of findings. Subsequently, in the phase of communication of the results, the final audit report was prepared and presented to the Rector of the Institution containing the results of the audit with the conclusions and recommendations for each of the findings evidenced. It is important to carry out the management audit since it indicates that it is a tool to evaluate the processes in order to promote the development of the organization where it involves the management, administrative, teaching and student personnel.